Population transcriptomics reveals a potentially positive role of expression diversity in adaptation. Issue 3 (2nd December 2014) - Xu, Qin; Xing, Shilai; Zhu, Caiyun; Liu, Wei; Fan, Yangyang; Wang, Qian; Song, Zhihong; Yang, Wenhui; Luo, Fan; Shang, Fei; Kang, Lifang; Chen, Wenli; et al.
Abstract While it is widely accepted that genetic diversity determines the potential of adaptation, the role that gene expression variation plays in adaptation remains poorly known. Here we show that gene expression diversity could have played a positive role in the adaptation of Miscanthus lutarioriparius. RNA‐seq was conducted for 80 individuals of the species, with half planted in the energy crop domestication site and the other half planted in the control site near native habitats. A leaf reference transcriptome consisting of 18, 503 high‐quality transcripts was obtained using a pipeline developed for de novo assembling with population RNA‐seq data. The population structure and genetic diversity of M. lutarioriparius were estimated based on 30, 609 genic single nucleotide polymorphisms. Population expression (Ep) and expression diversity (Ed) were defined to measure the average level and the magnitude of variation of a gene expression in the population, respectively. It was found that expression diversity increased while genetic diversity decreased after the species was transplanted from the native habitats to the harsh domestication site, especially for genes involved in abiotic stress resistance, histone methylation, and biomass synthesis under water limitation. The increased expression diversity could have enriched phenotypic variation directly subject to selections in the new environment.